Design, Fabrication and Performance Evaluation of a Photobioreactor for the Cultivation of Chlorella vulgaris (Beijerinck) (The Philippine Journal of Crop Science, 2013)
A 21-L algal culture feed capacity externally illuminated vertical-column draft-tube airlift photobioreactor was designed and fabricated for cultivating Chlorella vulgaris (Beijerinck), a micro algae that has a potential as substrate for biodiesel production. The glass photobioreactor was composed of the outer tube, draft tube, and airduct. Vespa SF 201P compressor was used as aerators and eight 36W Philips cool white fluorescent lamps as light source. Performance evaluation and design modification of the photobioreactor were conducted to improve its efficiency through the installation of a more efficient sampling mechanism and manipulating the sparger system. Mixture of air with 2.25% carbon dioxide was also infused into the reactor. Calibration of the optical density of microalgal culture at 425 mn and determination of the cell dry weight relationship were conducted. The experiment determined the growth curve and growth rate of C. vulgaris. The stationary phase was achieved after 10d with a growth rate of 0.2537 d-1and a doubling time of 3.94 d. The data obtained in Run B (growth rate) were used as a basis in the continuous operation of the photobioreactor. The feed rate computed was 3.855 L. d-1. The optical density inside the reactor and in the harvest was monitored. Therefore, the externally-illuminated vertical-column draft -tube airlift photobioreactor is suitable for a large-scale cultivation of C. vulgaris and can be operated continuously for a minimum of 30 d through the careful monitoring of the flowrate.